Synthesis and Characterization of Novel Aromatic Polyamides Containing Pyridine Heterocyclic Ring and Schiff-Base - Mutar, Mohammed A.; Abdul-Nebi, Mohammed H. (Al-Qadisiyah Journal of Pure Science, 2017)
Six new aromatic polyamides Par1-Par6 were prepared by direct Yamazaki’s polycondensation reaction of 4-Phenylenediacrylic acid (PPDAA) with two new aromatic Schiff-Base diamine monomers 2,6-bis[(4-amino-2,6-dimethylphenyl)methylene]diaminopyridine (BADMDP), 1,4-bis(6-aminopyridin-2-ylimino)dimethylenebenzene (BAPIDB); and Phthalic acid (PA) with four new diamine monomers containing pyridine heterocyclic group and bearing bulky aromatic pendant groups in the 4-position of the pyridine ring 4-(4-amino-2,6-dimethylphenyl)-2,6-bis(4-aminophenyl)pyridine (ADPBAP), 4-(2-hydroxyphenyl)-2,6-bis(4-aminophenyl)Pyridine (HPBAP), 4-(4-chlorophenyl)-2,6-bis(4-aminophenyl)pyridine (CPBAP), and 4-(4-(2,6-bis(4-aminophenyl) pyridin-4-yl)phenyl)-2,6-bis(4-aminophenyl)pyridine (BAPPBAP) in the presence of CaCl2 in Pyridine and Triphenyl phosphite (TPP) as condensing agents in N-methyl-2-Pyrolidinone (NMP) as solvent. 4-Phenylenediacrylic acid (PPDAA) was prepared by the condensation reaction of Terephthalaldehyde with Malonic acid in the presence of pyridine. The monomers were characterized by Fourier transform infrared (FTIR), and Nuclear magnetic resonance (1H-NMR). The resulting polyamides were characterized by Fourier transform infrared (FTIR), and Nuclear magnetic resonance(1H-NMR); and their physical properties including solubility, thermal stability and thermal behavior were studied as well. All of these new polymers show very good solubility in polar aprotic solvents and excellent thermal stability.